EFFECT OF FOUR CRUDE PLANT EXTRACTS ON GASTROINTESTINAL NEMATODES OF GOATS - Shelembe, Lindani; Moyo, Mehluli; Christopher Mhlongo, Lindokuhle; Verla Nsahlai, Ignatius (Chilean Journal of Agricultural & Animal Sciences, 2026)
The search for alternative control methods against gastrointestinal nematodes is intensifying due to anthelmintic drug resistance in small ruminants. This study evaluated the effect of four crude plant extracts (Aloe forex Mill., Clerodendrum glabrum, Elephantorrhiza elephantina, and Othonna natalensis) on gastrointestinal nematodes of goats using four concentrations: 4, 8, 12 and 16% (m/v). A control treatment (0% extract) was also included. Faecal samples from five goats were incubated for seven days to isolate L3 larvae. Isolation of L3 larvae from faecal samples was performed using the Baermann technique. Anthelmintic efficacy for all four dose levels of each plant species was significantly different (P<0.0001) from the control treatments. All crude plant extracts showed the highest efficacy at the highest concentration used (16% m/v) and the lowest efficacy at the lowest concentration (4% m/v). Among the crude plant extracts, Elephantorrhiza elephantina had the highest efficacy (80%) across concentrations, whereas Othonna natalensis exhibited the lowest efficacy. The selected crude plant extracts decreased gastrointestinal nematodes in a dose-dependent manner, but the magnitude of efficacy varied among the extracts.